Fast NMDA transmission and non-linear synaptic interactions in a sensory feedback pathway. - Plant, James Richard. (University of Ottawa (Canada), 1994)
Excitatory amino acid (EAA) neurotransmitters are extensively utilized at excitatory synapses throughout the vertebrate nervous system, with functional diversity being conferred by multiple forms of EAA receptors. Non-NMDA ionotropic EAA receptors (Kainate and AMPA) have typically been ascribed roles as mediators of fast neural transmission, with NMDA receptors hypothesized to contribute to slower processes such as temporal integration and synaptic plasticity. Employing extracellular field potentials, current source density analysis, and intrasomatic and dendritic recordings, the present studies demonstrated the relative contribution of non-NMDA and NMDA receptors to sensory feedback synapses within a highly stratified in vitro slice preparation of the electrosensory lateral line lobe (ELL) of the weakly electric fish Apteronotus leptorhynchus. Results confirmed a significant contribution of both a non-NMDA, and a fast NMDA component to EPSPs evoked by stimulation of the tractus stratum fibrosum (tSF) pathway. A voltage-dependent synaptically-mediated persistent Na$\sp+$ (slow) component of the tSF-evoked EPSP interacts with both fast NMDA and non-NMDA components, producing highly non-linear "thresholding" behaviour at the tSF synapses within the ventral molecular layer (VML) of the ELL. When viewed within the context of the in vivo physiology of this sensory feedback pathway, the complex response properties of the VML synapse suggests a rich diversity in EAA receptor/channel characteristics giving rise to dynamic functional properties which are consistent with its previously hypothesized role as a mediator of attentional processes within the electrosensory system.
Keywords: Biology, Neuroscience.